2016
DOI: 10.1024/0301-1526/a000528
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of extracranial carotid artery aneurysms

Abstract: Abstract. Background: We present the methods and results of the surgical management of extracranial carotid artery aneurysms (ECCA). Postoperative complications including early and late neurological events were analysed. Correlation between reconstruction techniques and morphology of ECCA was assessed in this retrospective study. Patients and methods: In total, 32 reconstructions of ECCA were performed in 31 symptomatic patients with a mean age of 59.2 (range 33 - 84) years. The causes of ECCA were divided amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Patients with ECAA are at high risk of ischemic stroke due to distal embolic occlusion secondary to dislodgement of thrombus in the aneurysm sac. 16 In the present case series, 37.5% patients (3/8) suffered from cerebral ischemic symptoms. Moreover, internal CCF occurred in one patient after endovascular of ECAA in the present study, which indicated that cerebral hemodynamic changes also contributed to cerebrovascular accident.…”
Section: Discussionmentioning
confidence: 46%
“…Patients with ECAA are at high risk of ischemic stroke due to distal embolic occlusion secondary to dislodgement of thrombus in the aneurysm sac. 16 In the present case series, 37.5% patients (3/8) suffered from cerebral ischemic symptoms. Moreover, internal CCF occurred in one patient after endovascular of ECAA in the present study, which indicated that cerebral hemodynamic changes also contributed to cerebrovascular accident.…”
Section: Discussionmentioning
confidence: 46%
“…Thus, we have concluded that MDA can serve as a linker to bind PAMAM based macromolecules onto a collagen scaffold covalently. Collagen based fibrin sealants have been tested for use as topical hemostatic agents and currently such patches are used by surgeons in variety of medical conditions …”
Section: Resultsmentioning
confidence: 99%
“…15 aneurysms -none bilateral-in a 20-years period, Rosset, et al [8]. 25 aneurysms among 1936 carotid reconstructions -none bilateral-in a 18-years period, and more recently, Jan Paweł Skora, et al [9]. 32 aneurysms-1 of them bilateral (6,25%) in a 26-years period).…”
Section: Discussionmentioning
confidence: 98%